DETERMINAN KEPATUHAN WAJIB PAJAK BADAN DENGAN NIAT SEBAGAI PEMEDIASI DARI PERSPEKTIF PLANNED BEHAVIOUR THEORY - Rachmawati Meita Oktaviani (Jurnal Bisnis dan Ekonomi, 2015)
This study aims to examine and analyze of attitude, subjective norm and perceived behavioral control with intention as intervening variabel to tax compliance. Population in this study is tax professional in KPP Semarang Barat. The selection for sampling method is convenience sampling or sampling which selection by easyer. The samples echievement is 86 respondents. Technique analyze for data is regression with path analyze. Finding of this research indicated the effect of attitude and perceived behavioral control influential toward taxpayer intention, subjective norm not influential toward taxpayer intention. Attitude,subjectif norm and perceived behavioral control influential toward tax compliance, intention not influential toward tax compliance.Keywords: attitude, subjective norm, perceived behavioral control, intention, tax compliance